Development Of Glass Coating Using Liquid Epoxidised Natural Rubber - Karthini, Kanestion (2012)
The purpose of this study on glass coating using ENR is to study the development of glass coating. The ENRs are selected as their moderate cost, environmentally friendly, great adhesion properties, and easily produced thru a simple and quite rapid route using peroxy acid onto NR (Natural Rubber). The experiment including determine drying time of the LENR (Liquid Epoxidized Natural Rubber) coating at various ratio 1:15, 2:47, 2.5:50, 3:54, 4:60, 5:72 and compare drying at ambient temperature, at 400C and 500C and find out the physical properties of 25 mol% epoxidation LENR (Liquid Epoxidized Natural Rubber) coating viscosity, pH and density at various ratio. The adhesion test was also performed to determine how well LENR coating is bonded to the glass. In this research, the experiment was completed by determining the pH, viscosity and density of samples using Gas Pycnometer, pH meter and Viscometer. For the adhesion test a peel test method was conducted revealing the quality of coating. The experimental running proved that the most convenient sample coating compare from the entire composition ratio, sample E, ratio 4:60 is the coating with average viscosity 631cP and pH 8.55 which act as alkaline coating that possibly protect the glass and have less environment impact. The density of sample E coating is 0.895g/cm3. Furthermore, the cure time of the coating is 360s at 30⁰C, 240s at 40⁰C and 180s 50⁰C that higher drying temperature result in short dry time. Also the hydrophobic property is an advantage for coating to protect glass. The result of this study is helpful to provide specific guidance in selection for developing high quality glass coating using LENR.